Regional Pop Music in Indonesia - Aryandari, Citra; Setyawan, Aris (Grenek: Jurnal Seni Musik, 2025)
Music is an essential part of our cultural life, a power to enrich our lives, build relationships between people, and shape identities and places. Indonesia's contemporary artistic and cultural life is very diverse, considering that Indonesia has a wide geographical area in Southeast Asia, with more than 17,000 islands “ and is the 4th most populous country in the world. Indonesia has a music landscape that is increasing. Some music is Karawitan from Java and Bali, Keroncong in Java, and Music with Sape from Kalimantan to Malay music in most areas of Sumatra. Indonesian musicians combine the elements of traditional music with elements of pop music. This paper will discuss how pop music from urban areas is combined with traditional music from each region in Indonesiaand then gives a new genre known as musik pop daerah (regional pop music)”the methodology used for this paper qualitative methodwith literature study. The result showed that pop music is a sign that culture”or, in this case, music”is fluid and can change according to the times.